Acute Vision Loss Secondary to Epidural Blood Patch: Terson Syndrome. Issue 2 (March 2016) - Pagani-Estévez, Gabriel L.; Chen, John J.; Watson, James C.; Leavitt, Jacqueline A.
Abstract : Background and Objectives: Lumbar epidural blood patch (EBP) is a commonly used procedure to treat postdural puncture headache. We present a case of vision loss immediately following an EBP. Case Report: A 49-year-old woman with idiopathic intracranial hypertension received an EBP for postdural puncture headache at an outside facility without fluoroscopic guidance and in the seated position. The patient experienced syncope during the procedure as 25 mL of autologous blood was rapidly injected. The patient regained consciousness and described bilateral vision loss. Brain magnetic resonance imaging was negative for hemorrhage. Dilated fundus examination revealed significant, bilateral retinal and vitreous hemorrhage consistent with Terson syndrome. Conclusions: This patient developed Terson syndrome as an immediate EBP complication. Iatrogenic Terson syndrome has been previously described with epidural space saline and anesthetic injections, but not EBP. Of 11 reported cases, 10 were female, and 9 had complete vision recovery. Previous studies have demonstrated that epidural space injection increases subarachnoid pressure in a volume- and rate-dependent fashion. An abrupt increase in subarachnoid space pressure likely led to retinal hemorrhage by compromising retinal venous drainage. This is the first known case of Terson syndrome caused by EBP. Injectate volume should be minimized, and a slow rate of injection pursued. The anesthesiologist, pain interventionist, and ophthalmologist should be aware of this rare but disabling complication and consider taking extra precautions when consenting patients for EBP with vision compromise or comorbidities concerning for elevated intracranial pressure.